7T MRI in focal epilepsy with unrevealing conventional field strength imaging. (18th January 2016) - De Ciantis, Alessio; Barba, Carmen; Tassi, Laura; Cosottini, Mirco; Tosetti, Michela; Costagli, Mauro; Bramerio, Manuela; Bartolini, Emanuele; Biagi, Laura; Cossu, Massimo; Pelliccia, Veronica; Symms, Mark R.; et al.
Summary: Objective: To assess the diagnostic yield of 7T magnetic resonance imaging (MRI) in detecting and characterizing structural lesions in patients with intractable focal epilepsy and unrevealing conventional (1.5 or 3T) MRI. Methods: We conducted an observational clinical imaging study on 21 patients (17 adults and 4 children) with intractable focal epilepsy, exhibiting clinical and electroencephalographic features consistent with a single seizure‐onset zone (SOZ) and unrevealing conventional MRI. Patients were enrolled at two tertiary epilepsy surgery centers and imaged at 7T, including whole brain (three‐dimensional [3D] T1 ‐weighted [T1W] fast‐spoiled gradient echo (FSPGR), 3D susceptibility‐weighted angiography [SWAN], 3D fluid‐attenuated inversion recovery [FLAIR]) and targeted imaging (2D T2 *‐weighted dual‐echo gradient‐recalled echo [GRE] and 2D gray–white matter tissue border enhancement [TBE] fast spin echo inversion recovery [FSE‐IR]). MRI studies at 1.5 or 3T deemed unrevealing at the referral center were reviewed by three experts in epilepsy imaging. Reviewers were provided information regarding the suspected localization of the SOZ. The same team subsequently reviewed 7T images. Agreement in imaging interpretation was reached through consensus‐based discussions based on visual identification of structural abnormalities and their likely correlation with clinical and electrographic data. Results: 7T MRI revealed structural lesions in 6 (29%) of 21 patients. The diagnostic gain in detection was obtained using GRE and FLAIR images. Four of the six patients with abnormal 7T underwent epilepsy surgery. Histopathology revealed focal cortical dysplasia (FCD) in all. In the remaining 15 patients (71%), 7T MRI remained unrevealing; 4 of the patients underwent epilepsy surgery and histopathologic evaluation revealed gliosis. Significance: 7T MRI improves detection of epileptogenic FCD that is not visible at conventional field strengths. A dedicated protocol including whole brain FLAIR and GRE images at 7T targeted at the suspected SOZ increases the diagnostic yield.